Raytheon long life cryocoolers for future space missions. (December 2017) - Conrad, T.; Schaefer, B.; Bellis, L.; Yates, R.; Barr, M.
Highlights: The Low Temperature Raytheon Stirling/Pulse Tube 2-stage Hybrid (LT-RSP2) cryocooler is designed for operation below 10 K. A production LT-RSP2 has now been integrated with control electronics and an optical bench. Details of its performance are presented. The Raytheon Advanced Miniature (RAM) cryocooler is a single stage pulse tube cryocooler designed for relatively low cost and rapid manufacturing. Two production RAM cryocoolers have been built and tested. An additional brassboard RAM expander which is optimized for lower temperature operation has been produced. Abstract: Over the last several years, Raytheon has made significant advances on two long-life cryocoolers designed for efficient operation on space platforms. The first is the Low-Temperature Raytheon Stirling/Pulse Tube 2-stage (LT-RSP2) hybrid cryocooler, which is capable of providing simultaneous cooling at 55 K and 10 K nominal first and second stage temperatures. The LT-RSP2 design was finalized in mid-2009, with fabrication of the prototype unit taking place in late 2009 and early 2010 and execution of the production program in 2011–2015. During this period the LT-RSP2 has undergone extensive characterization testing and has successfully been integrated with an optical bench. The second cryocooler is the Raytheon Advanced Miniature (RAM) cryocooler, a flight packaged single stage pulse tube cooler with an integrated surge volume and inertance tube. It has been designed for high frequency operation and has been fully optimized to make use of the Raytheon Advanced Regenerator, resulting in improved efficiency relative to previous Raytheon pulse tube coolers. In this paper, aspects of both the LT-RSP2 and RAM mechanical and thermodynamic designs will be presented as well as information regarding their capabilities and performance.